The Impact of Integration on Application Success and Customer Satisfaction in Mobile Device Platforms - Benedict Bender (Business & Information Systems Engineering, 2020)
Digital software platforms allow third parties to develop applications and thus extend their functionality. Platform owners provide platform boundary resources that allow for application development. For developers, platform integration, understood as the employment of platform resources, helps to realize application functionality effectively. Simultaneously, it requires integration effort and increases dependencies. Developers are interested to know whether integration contributes to success in hypercompetitive platform settings. While aspects of platform participation have been studied, research on a comprehensive notion of integration and related implications are missing. By proposing a platform integration model, this study supports a better understanding of integration. Concerning dynamics related to integration, effects were tested using information from over 82,000 Apple AppStore applications. Regression model analysis reveals that application success and customer satisfaction is positively influenced by platform integration. To achieve superior results, developers should address multiple aspects of integration, such as devices, data, the operating system, the marketplace as well as other applications, and provide updates. Finally, the study highlights the importance for all platform participants and their possibilities to employ integration as a strategic instrument.
Keywords: 000; Integration; Digital platforms; Boundary resources; Application success; Customer satisfaction; Mobile device platforms